Communication in the classroom: Practice and reflection of a mathematics teacher - Martinho, Maria Helena (2011)
This paper discusses the conceptions, practices and reflections about practices of a mathematics teacher, Maria, with respect to classroom communication and their change during the activity of a collaborative project involving a researcher and two other mathematics teachers. The case study of this teacher, who teaches at grades 5-6, draws on interviews and participant observation of the collaborative project meetings. The results show the relevance of the project to develop the teacher’s understanding of communication issues in her classroom, putting her practices under scrutiny, and developing richer communication processes between her and her students.